(untitled) (Acta Judicial Journal, 2022)
Disability is one of the great challenges, present and future, facing humanity. Disability-friendly legislation must start from the value of their difference and bear in mind that it affects not only the living conditions of millions of people, ten percent of the world’s population, but also their dignity, freedom, development of personality and equality with other people. In accordance with Article 13 of the 2006 New York Convention, ratified by Spain in 2008, initialed Access to Justice, the States Parties shall ensure that persons with disabilities have access to justice on equal terms with other persons.